Forced vibration of the pre-stretched simply supported strip containing two neighbouring circular holes - Yahnioglu, Nazmiye; Akbarov, Surkay D. (SPRINGER, 2007)
Within the framework of the Three-Dimensional Linearized Theory of the Elastic Waves in Initially Stressed Bodies under plane-strain state the influence of the initial stretching of the simply supported plate strip containing two circular holes on the stress concentration around the holes caused by the action of the additional uniformly distributed normal dynamical (time-harmonic) forces on the plane of its upper face is studied. For the solution of the problem the FEM is employed. The numerical results on the stress concentration and the influence of the statical initial stresses and the frequency of the additional dynamical external forces frequency to this concentration are presented.
Keywords: dynamical (time-harmonic) stress field; initial stresses; plate-strip; forced vibration; STRESS; Engineering; Mechanics